Pivotal Trial of Enfortumab Vedotin in Urothelial Carcinoma After Platinum and Anti-Programmed Death 1/Programmed Death Ligand 1 Therapy - Rosenberg, Jonathan E. (J Clin Oncol, 2019)
PURPOSE: Locally advanced or metastatic urothelial carcinoma is an incurable disease with limited treatment options, especially for patients who were previously treated with platinum and anti–programmed death 1 or anti–programmed death ligand 1 (PD-1/L1) therapy. Enfortumab vedotin is an antibody–drug conjugate that targets Nectin-4, which is highly expressed in urothelial carcinoma. METHODS: EV-201 is a global, phase II, single-arm study of enfortumab vedotin 1.25 mg/kg (intravenously on days 1, 8, and 15 of every 28-day cycle) in patients with locally advanced or metastatic urothelial carcinoma who were previously treated with platinum chemotherapy and anti–PD-1/L1 therapy. The primary end point was objective response rate per Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1 by blinded independent central review. Key secondary end points were duration of response, progression-free survival, overall survival, safety, and tolerability. RESULTS: Enfortumab vedotin was administered to 125 patients with metastatic urothelial carcinoma. Median follow-up was 10.2 months (range, 0.5 to 16.5 months). Confirmed objective response rate was 44% (95% CI, 35.1% to 53.2%), including 12% complete responses. Similar responses were observed in prespecified subgroups, such as those patients with liver metastases and those with no response to prior anti–PD-1/L1 therapy. Median duration of response was 7.6 months (range, 0.95 to 11.30+ months). The most common treatment-related adverse events were fatigue (50%), any peripheral neuropathy (50%), alopecia (49%), any rash (48%), decreased appetite (44%), and dysgeusia (40%). No single treatment-related adverse events grade 3 or greater occurred in 10% or more of patients. CONCLUSION: Enfortumab vedotin demonstrated a clinically meaningful response rate with a manageable and tolerable safety profile in patients with locally advanced or metastatic urothelial carcinoma who were previously treated with platinum and anti–PD-1/L1 therapies.